Predicting users' return to virtual worlds: a social perspective. (15th May 2012) - Goel, Lakshmi; Johnson, Norman; Junglas, Iris; Ives, Blake
Abstract Virtual worlds or three‐dimensional computer‐based simulated environments have received considerable attention as platforms for entertainment, education and commerce. In contrast to a web site, for example, where a user interacts with a two‐dimensional site, virtual worlds provide a platform in which users can interact with other individuals, sometimes including strangers, within three‐dimensional environments. Virtual worlds afford a form of 'socialness' unlike many other technologies, often motivating a user – by virtue of these social experiences – to return. Drawing on the Spatial Model of Interaction and Awareness‐Attention Theory, we demonstrate that besides social aspects, which include social awareness and social perception, flow experience, which is the mental state of being fully absorbed and somewhat lost in time, is an essential ingredient in an individual's decision to return to a virtual world. We also demonstrate how characteristics of the technology are linked to the social aspects experienced in virtual worlds. A laboratory study conducted in a virtual world, Second Life, supports our assertions and identifies state predictors of flow that influence individuals' intentions to return to the virtual world environment.